Redefining Inheritance Justice: The Practice of Patah Titi and The Role of Substitute Heirs in Islamic Law in Sabang City, Aceh - Aulil Amri; Arifin Abdullah; Nur Muhajirah Siagian; Faisal Yahya; Nurul Fithria (QONUN: Jurnal Hukum Islam dan Perundang-undangan, 2026)
Inheritance issues are common in daily life, one of which is the patah titi system, formally referred to as substitute heirs. In Sabang City, Aceh, this concept is still practiced children whose parents die before the inheritance giver are considered ineligible to receive inheritance. This stems from the belief that such children are not specifically mentioned in the Qur’anic inheritance divisions, and thus, do not qualify to inherit from their grandparents. This study aims to explore the concept of patah titi in Sabang society and analyze it through Article 185 of the Compilation of Islamic Law (KHI) regarding substitute heirs. The research uses an empirical legal approach combined with statutory analysis. Findings show that the patah titi practice remains active in Gampong Kuta Timu, Sabang, despite existing legal provisions on substitute heirs in the KHI. Misunderstanding the meaning of patah titi has created more negative than positive impacts not only in the inheritance process but also in weakening family bonds. In practice, grandchildren affected by patah titi may receive assets through grants, whereas grandchildren recognized as substitute heirs receive assets through inheritance.